Impact Of Gender Roles And Business Type: A Study Of Entrepreneurship Among AIM Microcredit Borrowers - Mohd Zahari, Maimun; Selamat, Nor Hafizah; Endut, Noraida; Karupaiah, Premalatha; Mohd Isa, Salmi; Fernando, Yudi (2016)
Gender roles and business type are two important elements that determine the success of an entrepreneurship activity. The purpose of this paper is to explore the impact of those two elements on the success of entrepreneurship activities of AIM microcredit borrowers. Data was collected based on a survey with a total of 133 AIM borrowers in Selangor, Malaysia. It consists of 71 men borrowers and 62 women borrowers. The research findings show a significance difference in the impact of gender roles and business type on the success of men and women borrowers. The findings of the survey suggest that impact of gender roles are more significant on the success of women borrowers compared to the men borrowers while the type of business conducted which varies from public transportation business to food and beverage business determines the success of men borrowers as well as the women borrowers. It is argued that gender roles have greater influence on the success of female borrowers compare to men borrowers whereas the choice of type of business differ between male and female borrowers. Female borrowers concentrated more on food and beverages and tailoring business while most male borrowers involved in public transportation business as taxi drivers. This study is expected to highlight the difference in entrepreneurship success determinants between men and women borrowers of AIM.